Carbon‐bridged Tri(cyclopentadiene): Synthesis and Coordination with Ytterbium. Issue 12 (7th November 2014) - Sha, Lin; Li, Li; Yuan, Fugen
Abstract Reaction of a mixture of 1, 1‐bis(cyclopentadienyl)cyclohexane and pentamethylenefulvene with metallic sodium in THF led to a mixture of cyclohexylidene‐bridged bis(cyclopentadienyl) sodium and two‐cyclohexylidene‐bridged tri(cyclopentadienyl) sodium. Reaction of the salt solutions with anhydrous YbCl3 in THF afforded a ytterbium complex mixed‐ligated by bridged bis(cyclopentadienide) and bridged tri(cyclopentadienide).